JURIDICAL ISSUES IN ENFORCING FINAL AND BINDING ARBITRAL AWARDS IN INDONESIA - Muhammad Nur Rakhmad; Prof. Dr. Prasetijo Rijadi; Dr. Sholehuddin Sholehuddin (jfpublisher, 2025)
Arbitration constitutes a form of Alternative Dispute Resolution (ADR) conducted outside the judicial framework, specifically addressing disputes related to commerce and trade at both domestic and international levels. For arbitration to be applicable, there must be a contractual agreement to utilize an arbitration institution. Despite the widespread adoption of arbitration institutions for resolving business disputes, their efficacy, particularly in the enforcement of arbitral awards, remains a contentious issue. Arbitral awards may be executed voluntarily, provided there is full awareness and good faith. In instances where voluntary compliance is absent, an application may be submitted to the Chief Judge of the District Court to enforce compliance upon the respondent. The practical execution of these awards often encounters significant challenges, including prolonged durations and substantial costs, which can erode legal certainty.This study aims to examine the issues surrounding the enforcement of final and binding arbitral awards in Indonesia. The research method used is normative legal research which is descriptive in nature with a statutory approach and a conceptual approach which is then supported by empirical research to enrich the depth of the research process. The results of this research are the obstacles and legal efforts in overcoming the execution of final and binding arbitration awards.